2013
DOI: 10.2337/dc13-0229
|View full text |Cite|
|
Sign up to set email alerts
|

Increased Risk of Cognitive Impairment in Patients With Diabetes Is Associated With Metformin

Abstract: OBJECTIVETo investigate the associations of metformin, serum vitamin B12, calcium supplements, and cognitive impairment in patients with diabetes.RESEARCH DESIGN AND METHODSParticipants were recruited from the Primary Research in Memory (PRIME) clinics study, the Australian Imaging, Biomarkers and Lifestyle (AIBL) study of aging, and the Barwon region of southeastern Australia. Patients with Alzheimer disease (AD) (n = 480) or mild cognitive impairment (n = 187) and those who were cognitively intact (n = 687) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
242
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 331 publications
(256 citation statements)
references
References 40 publications
6
242
2
6
Order By: Relevance
“…We thank Goodarzi (1) for his interest in our work (2) and recognize that we agree with most of the criticisms leveled at our study. Indeed, most of the points raised were acknowledged in our original work.…”
supporting
confidence: 74%
“…We thank Goodarzi (1) for his interest in our work (2) and recognize that we agree with most of the criticisms leveled at our study. Indeed, most of the points raised were acknowledged in our original work.…”
supporting
confidence: 74%
“…This malabsorption ultimately leads to a reduction of serum Vitamin B 12 [41][42][43][44][45]. Hence, some researchers were calling attention to the monitoring of Vitamin B 12 concentration in the diabetic patients treated with metformin, and suggested Vitamin B 12 supplementation could be considered in patients with Vitamin B 12 deficiency [3,46,47], although some authors still doubt the clinical significance of this reduction [48,49]. A recent clinical trial suggested that the metformin-associated reduction of the serum Vitamin B 12 was due to the increased transportation and utility of Vitamin B 12 by cells stimulated by metformin [50].…”
Section: Discussionmentioning
confidence: 99%
“…Stopnja znižanja ravni vitamina B12 je odvisna od skupnega odmerka (95). Klinični pomen opisane spremembe je sicer še vedno stvar razprave; vsaj nekatere raziskave pa so pokazale, da bi lahko nižja koncentracija vitamina B12, povzročena z metforminom, vodila tudi razvoj v megaloblastne anemije (96), kognitivnega upada in napredovanja diabetične periferne nevropatije (97). Zaradi velikih zalog vitamina B12 se pomanjkanje izrazi šele po večletni uporabi metformina.…”
Section: Neželeni Učinki Na Raven Vitamina B12unclassified